2011
DOI: 10.1105/tpc.111.086140
|View full text |Cite
|
Sign up to set email alerts
|

Malonyl-CoA Synthetase, Encoded by ACYL ACTIVATING ENZYME13, Is Essential for Growth and Development of Arabidopsis      

Abstract: Malonyl-CoA is the precursor for fatty acid synthesis and elongation. It is also one of the building blocks for the biosynthesis of some phytoalexins, flavonoids, and many malonylated compounds. In plants as well as in animals, malonyl-CoA is almost exclusively derived from acetyl-CoA by acetyl-CoA carboxylase (EC 6.4.1.2). However, previous studies have suggested that malonyl-CoA may also be made directly from malonic acid by malonyl-CoA synthetase (EC 6.2.1.14). Here, we report the cloning of a eukaryotic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 58 publications
(81 reference statements)
3
83
0
Order By: Relevance
“…One hundred milligrams of dried endosperm flour were used for metabolite extraction according to Chen et al (2011) with some modification. Briefly, dried extracts were dissolved in mixed solution of water/isopropanol/methanol (1:3:6, v/v).…”
Section: A-ketoglutaric Acid and Oxaloacetate Analysismentioning
confidence: 99%
“…One hundred milligrams of dried endosperm flour were used for metabolite extraction according to Chen et al (2011) with some modification. Briefly, dried extracts were dissolved in mixed solution of water/isopropanol/methanol (1:3:6, v/v).…”
Section: A-ketoglutaric Acid and Oxaloacetate Analysismentioning
confidence: 99%
“…Upon electrophoresis in a SDS-polyacrylamide gel and visualization with Coomassie blue stain, the recombinant protein was estimated to be >90% pure ( Figure 1A). A preparation was tested against 10 carboxylic acids at pH 7.5 and 300 mM substrate, using a spectrophotometric, coupled-enzyme assay (Ziegler et al, 1987;Chen et al, 2011). In these initial assays, His-AAE3 showed high activity only with oxalate, 5.8 mmol/min/mg protein.…”
Section: Aae3 Functions As An Oxalyl-coa Synthetasementioning
confidence: 99%
“…Some CoA synthetase enzymes activate a wide range of substrates in vitro; examples include several long-chain acyl-CoA synthetases that can use multiple fatty acids as substrates (Shockey et al, 2002) and some 4-coumaroyl-CoA ligase-like proteins that were found to use both fatty acids and jasmonate precursors as substrates in vitro (Kienow et al, 2008). By contrast, other AAEs are very specific for their substrate, such as the malonyl-CoA synthetase encoded by AAE13 (Chen et al, 2011). The high specificity of the His-AAE3 recombinant enzyme for oxalate identifies AAE3 as the first gene cloned from any organism to encode oxalyl-CoA synthetase activity.…”
Section: Aae3 Is An Oxalyl-coa Synthetase and Is Required For Oxalatementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the Arabidopsis malonyl- CoA synthase gene give rise to severe growth inhibition and low fertility (Chen et al 2011); similar effects are observed in ABC-ox, suggesting that growth inhibition in ABC-ox is attributable to low malonyl-CoA. To achieve high PHA yield, we must organize the PHA biosynthetic pathway and endogenous metabolic pathways to avoid interference.…”
mentioning
confidence: 99%